2021
DOI: 10.1002/cphc.202100135
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Resolved Kinetic Model of Parahydrogen Induced Polarisation (PHIP) in a Microfluidic Chip

Abstract: We report a spatially resolved kinetic finite element model of parahydrogen-induced polarisation (PHIP) in a microfluidic chip that was calibrated using on-chip and off-chip NMR data. NMR spectroscopy has great potential as a read-out technique for lab-on-a-chip (LoC) devices, but is often limited by sensitivity. By integrating PHIP with a LoC device, a continuous stream of hyperpolarised material can be produced, and mass sensitivities of pmol ffi ffi s p have been achieved. However, the yield and polarisatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Finite element simulations of the chip have shown that when methanol is flowed through the chip at 10 μL min –1 at a pressure of 5 bar, only 10 mM of hydrogen dissolves in the fluid. 64 Since in this work water was used as the solvent, the concentration of hydrogen dissolved is expected to be lower due to poorer solubility of hydrogen in water. Modifications to the apparatus to improve the H 2 uptake and yield of the reaction are currently underway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finite element simulations of the chip have shown that when methanol is flowed through the chip at 10 μL min –1 at a pressure of 5 bar, only 10 mM of hydrogen dissolves in the fluid. 64 Since in this work water was used as the solvent, the concentration of hydrogen dissolved is expected to be lower due to poorer solubility of hydrogen in water. Modifications to the apparatus to improve the H 2 uptake and yield of the reaction are currently underway.…”
Section: Resultsmentioning
confidence: 99%
“…The low yield of the reaction is most likely due to the limited uptake of hydrogen into the flowing solution. Finite element simulations of the chip have shown that when methanol is flowed through the chip at 10 μL min –1 at a pressure of 5 bar, only 10 mM of hydrogen dissolves in the fluid . Since in this work water was used as the solvent, the concentration of hydrogen dissolved is expected to be lower due to poorer solubility of hydrogen in water.…”
Section: Resultsmentioning
confidence: 99%
“…An emerging research area that is mainly pursued at high magnetic fields is the integration of PHIP into lab-on-a-chip devices. , The advantage offered by working at a microfluidic scale ( i.e. , with sample volumes on the order of microliters) is in the much higher degree of experimental control that can be leveraged, in terms of sample contact time with pH 2 , molecular diffusion, temperature, and pressure.…”
Section: Other Promising Developmentsmentioning
confidence: 99%
“…38 However, the yield obtained in both cases falls short of the requirements for biological applications, particularly since further transformations such as purification and cleavage are required to effectively utilise the hyperpolarized material. To understand the interplay of the chemical, spatial and spin dynamics occurring on the microfluidic device proposed by Eills et al Ostrowska et al 39 developed a finite element model of reaction and found that insufficient uptake of hydrogen was the limiting factor of the reaction.…”
Section: Introductionmentioning
confidence: 99%